2015
DOI: 10.1080/21645698.2015.1091553
|View full text |Cite
|
Sign up to set email alerts
|

CRISPRing into the woods

Abstract: The CRISPR/Cas9 technology is a welcome breakthrough for genome editing, owing to its precision, efficiency, versatility and ease of adoption. We recently reported the first application of CRISPR/Cas9 for biallelic mutations in stably transformed Populus, extending the species range of this powerful technology to woody perennials. An underappreciated obstacle in genome editing of outcrossing species is the frequent occurrence of sequence polymorphisms that can render CRISPR/Cas9 unproductive. We discuss experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…Next to that, structural variability, such as density or MFA, between transgenics and the WT should be small, whereas differences in lignin content have to be high enough for a detectable influence. Using the new CRISPR/Cas9 gene‐editing technology, which has been demonstrated to work efficiently in poplar (Tsai et al ., ), at least the spatial variability in the efficiency of gene downregulation can be overcome (Zhou et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Next to that, structural variability, such as density or MFA, between transgenics and the WT should be small, whereas differences in lignin content have to be high enough for a detectable influence. Using the new CRISPR/Cas9 gene‐editing technology, which has been demonstrated to work efficiently in poplar (Tsai et al ., ), at least the spatial variability in the efficiency of gene downregulation can be overcome (Zhou et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in the cultivar Khalas about 0.9 million new SNPs have also been reported. A high frequency of SNPs in the coding region is also reported from other woody perennial trees such as Populus trichocarpa, Populus tremula , and Eucalyptus ( Tsai and Xue, 2015 ). Because, most of the plant models used for GE through CRISPR/Cas9 are highly homozygous, therefore few studies are available, which addressed sequence polymorphisms.…”
Section: The Limitations Of Date Palm Genome Editingmentioning
confidence: 83%
“…Analysis of the RNA-guided genome-editing events demonstrated that 30 of 59 PCR clones were homozygous mutants, 2 of 59 were heterozygous mutants, and the mutation efficiency at these target sites was estimated to be 51.7 % (Fan et al 2015). The CRISPR/Cas9 system was better than previous approaches for determining functional redundancy of paralogous genes that are prevalent in plant genomes, indicating that CRISPR/Cas9 will accelerate not only basic research but also crop improvement progress (Tsai and Xue 2015).…”
Section: Populusmentioning
confidence: 98%
“…When RNA-guided genome editing and targeted gene mutation via the CRISPR/Cas9 system was used to edit the genome of Populus tomentosa, four gRNAs were designed to target distinct poplar genomic sites of the phytoene desaturase gene 8 (PtoPDS) that are followed by the protospacer-adjacent motif (Fan et al 2015;Tsai and Xue 2015). After Agrobacterium-mediated transformation, an obvious albino phenotype was observed in transgenic poplar plants.…”
Section: Populusmentioning
confidence: 99%